Research of One Type of Exotic Options on Extremes in the Diffusion Model of (B; S) - Finance Market; Proceedings of the Second International Conference on innovative Computing, Information and Control (ICICIC), Kumamoto, Japan, 5-7 September, 2007 - Rozhkova S. V. Svetlana Vladimirovna
В фонде НТБ ТПУ отсутствует